Dynamics of thioredoxin 1, thioredoxin reductase 1 and glutathione-S-transferase Pi content in the spleen and liver of rats during the latent period of growth and metastasis of sarcoma C45 - E. I. Surikova; E. M. Frantsiyants; I. V. Kaplieva; I. V. Neskubina; E. G. Shakaryan; A. V. Snezhko; E. N. Kolesnikov; V. A. Bandovkina; L. K. Trepitaki; Yu. A. Petrova; N. S. Lesovaya; M. A. Engibaryan; et al. (Исследования и практика в медицине, 2025)
Purpose of the study. To examine the dynamics of the content of thioredoxin 1 (Trx1), thioredoxin reductase 1 (TR1), and glutathione  S-transferase Pi (GST Pi) in the spleen and liver during the latent period of growth and metastasis of C45, which occurs approximately one to two weeks after tumor transplantation.Materials and methods. The experiment was conducted on 28 male rats of a white, nonlinear strain. A model of hematogenous metastasis to the liver was created by transplanting sarcoma 45 (C45) into the spleen, which was previously dislocated under the skin three weeks prior to the commencement of the experiment. The experimental Groups were as follows: Group 1 (n = 7) comprised intact rats; Group 2 (n = 7) comprised rats in which the spleen was dislocated under the skin; Group 3 (n = 7) comprised rats one week later; and Group 4 (n = 7) comprised rats two weeks later. In each case, the rats had undergone transplantation of C45 into the spleen, which had been dislocated under the skin. The concentrations of Trx1, TR1, and GST Pi were quantified in spleen and liver homogenates through the use of enzyme linked immunosorbent assay (ELISA).Results. Group 1 exhibited a significantly elevated (p ≤ 0.01) Trx1 and TR1 level in the liver, at 8.3 and 3.4 times higher, respectively, in comparison to the spleen. Conversely, the GST Pi level did not demonstrate a notable discrepancy between the two organs. Group 2 exhibited elevated TR1 levels in the spleen and diminished TR1 and Trx1 levels in the liver relative to Group 1. In Group 3, spleen Trx1 and TR1 increased, while in Group 4, these levels were elevated by 1.7 (p ≤ 0.05) and 5.5 (p ≤ 0.001) times, respectively, compared to Group 1. Additionally, Group 4 exhibited lower GST Pi levels on average by 2. The results demonstrated a statistically significant increase in Trx1 and TR1 levels in Groups 3 and 4, with a threefold increase (p ≤ 0.05) in Groups 3 and 4 compared to Group 1. In the liver, Trx1 and TR1 levels were found to be 4.6 and 1.8 times lower ( p ≤ 0.001) in Group 3 compared to Group 1. In Group 4, Trx1 remained lower (2.9 times, p ≤ 0.01), while TR1 levels were restored to the level observed in Group 1, along with GST Pi.Conclusion. The initially greater significance of the Trx system for liver homeostasis than that of the spleen is obvious. During the latent period of C45 growth and metastasis, the antioxidant and redox regulating functions of the Trx system were activated in the spleen, while in the liver, it was inhibited, disrupting the antioxidant and redox homeostasis of the organ. The activity of detoxification and glutathionylation processes regulated by GST Pi decreased in the latent period in the spleen, while in the liver it corresponded to the level in the intact organ. The results reflect the possible mechanism of an imbalance in the protective metabolic systems of the liver during the latent period of metastasis, forming the basis for it.